Analisis Pembentukan Kata pada Berita Detik News yang Berjudul “Simak Visi Misi 4 Paslon di Pilgub Jabar 2024 dalam Debat Kedua” Edisi November 2024: Kajian Morfologi - Aini Fitri Rohmatul Ilmi; Putri Siti Aisya; Siti Umai Nazilah; Taswirul Afkar (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study analyses the morphological process in the news ‘Check out the Vision and Mission of 4 Candidates in West Java Gubernatorial Election 2024 in the Second Debate’ published by Detik News in the November 2024 edition. The purpose of this research is to find and understand the morphological structure used in the delivery of information related to the West Java governor election. The methodology of this research is descriptive qualitative approach. Information is collected through observation or observation done by reading the news and making notes. The results of the research show information on the use of affixation, namely the prefixes ber-, mem, men-, as well as the confixes me-kan, ke-an, pe-an, pe(r)-an. There is also information on the use of reduplication such as, children. And there is information on the use of composition such as the word new pair. It is intended that these findings can increase understanding of language use in the mass media.